Identification of Student Character Values in Class X Particle Dynamics Materials - Astalini Astalini; Darmaji Darmaji; Dwi Agus Kurniawan; Sri Wina Oktavia; Feliza Paramitha Sinaga; Neni Septiani; Nikma Nur Qoidah; Marcis Auzinsh (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
education, character education which aims to develop the ability of students to make good and bad decisions, maintain what is good and realize that goodness in everyday life wholeheartedly. This study aims to identify the impact that occurs on students if there is no character value in class X physics learning on particle dynamics material. The method used is a qualitative method. The instrument used is document study. The data collection technique is document study by collecting books and related literature. The sample used in this study is the material for class X in the Physics Teacher book curriculum 2013. The results of this study indicate that there are some character values that are not embedded in the particle dynamics material. This is because these values are not applied and directed at the ongoing learning. Of course, no character values in particle dynamics material can have a sustainable impact or long-term and short-term impacts that will be repeated by every student. It is hoped that in the future it can be further refined so that each character value can be listed and applied to learning so that it will build a better generation.